Adolescent Socioeconomic Status and Parent-Child Emotional Bonds: Reexamining Gender Differences in Mental Well-being during Young Adulthood. (March 2019) - Wilkinson, Renae; Andersson, Matthew A.
Links between elevated mental well-being in adulthood and higher social and economic resources growing up are well established. However, the role of gender remains unclear, especially whether gender influences how social and economic resources interact to produce disparities in mental well-being across young adulthood. Drawing on nationally representative longitudinal data, we illuminate gender differences in mental well-being, finding that young adult mental health advantages based in adolescent socioeconomic status pivot on parent-child emotional bonds for young men only. That is, for young adult men, lessened depressive symptom frequency linked to higher parental education only appears when perceived parent-child bonds are at least moderately close. This holds even after adjusting for earlier adolescent mental well-being, suggesting a stable mechanism across the transition to adulthood. Overall, our results uphold the argument that familial social and economic resources predict mental well-being during young adulthood while revealing that relevant mechanisms may differ by gender.